2021
DOI: 10.1158/0008-5472.can-21-0799
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Cancer-on-Chip Platform Predicts Drug Response Using Organotypic Tumor Slice Culture

Abstract: Conflictsof interest: CS, NG and WFQS are founders of BIOND Solutions B.V. (BI/OND). AO is employee of BIOND Solutions B.V. AvdS is a full-time employee of Philips Molecular Pathway Dx.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…The relevance of the method is now supported by PDX experiments. Chakrabarty et al [ 22 ] have shown that tumor-derived PDX provided a reliable predictive tool to anticipate the effect of treatment on tumors, in that case, to assess resistance to cisplatin in breast tumors. The limit for this approach is the amount of time necessary to grow the PDX, amounting to several weeks in mice, to be added to the time necessary for drug screening.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of the method is now supported by PDX experiments. Chakrabarty et al [ 22 ] have shown that tumor-derived PDX provided a reliable predictive tool to anticipate the effect of treatment on tumors, in that case, to assess resistance to cisplatin in breast tumors. The limit for this approach is the amount of time necessary to grow the PDX, amounting to several weeks in mice, to be added to the time necessary for drug screening.…”
Section: Discussionmentioning
confidence: 99%
“…We acquired the BIOND organ-on.chip system (inCHIPitℱ and comPLATEℱ) (BIOND Solutions B.V., Delft, The Netherlands). The inCHIPitℱ is produced using polydimethylsiloxane film supported by a silicon frame, and consists of a culture chamber that communicates with the underlying three 400 ”M-wide channels through 4 ”M-wide pores 25 To generate flow, chips are placed on the comPLATEℱ and this is connected to a pressure pump that generates 800 mbar of pressure, and pumps circulating medium from the reservoir through the tubing and towards the chip channels, producing an estimated flow rate across the porous membrane of 0.2 ”L/min. The system allows to maintain a constant flow thanks to the pressure regulator placed in the system, which ensures continuous fresh medium and stable shear stress.…”
Section: Methodsmentioning
confidence: 99%
“…We also confirmed that in vivo responses were mimicked in the OoC device: cisplatin sensitivity in the device was consistent the in vivo characteristics of breast cancer PDX models (Fig. 4), and androgendependent prostate tumors were sensitive to the anti-androgen apalutamide (Chakrabarty et al, 2022).…”
Section: Commentary Background Informationmentioning
confidence: 99%